반응가스 비율에 따른 탄소나노월의 성장특성 - 김성윤(Sung-Yun Kim); 강현일(Hyunil Kang); 최원석(Won Seok Choi); 정연호(Yeun-Ho Joung); 임윤식(Yonnsik Lim); 유영식(Youngsik Yoo); 황현석(Hyun Suk Hwang); 송우창(Woo-Chang Song) (전기학회 논문지 P권, 63(4), 2014)
Graphite electrodes are used for secondary batteries, fuel cells, and super capacitors. Research is underway to increased the reaction area of graphite electrodes used carbon nanotube (CNT) and porous carbon. CNT is limited to device utilization in order to used a metal catalyst by lack of surface area to improve. In contrast carbon nanowall (CNW) is chemically very stable. So this paper, microwave plasma enhanced chemical vapor deposition (PECVD) system was used to grow carbon nanowall (CNW) on Si substrate with methane ($CH_4$) and hydrogen ($H_2$) gases. To find the growth properties of CNW according to the reaction gas ratio, we have changed the methane to hydrogen gas ratios (4:1, 2:1, 1:2, and 1:4). The vertical and surficial conditions of the grown CNW according to the gas ratios were characterized by a field emission scanning electron microscopy (FE-SEM) and Raman spectroscopy measurements showed structure variations.